SELECTION METHOD FOR PARTNERSHIP TYPE IN THE OPERATION OF REGIONAL DISTRIBUTION CENTER BASED ON MULTI CRITERIA DECISION MAKING - (NIM: 23411038); Pembimbing :Dr. Ir. Sukoyo, M.T., SUTRISNO
The availability of reliable logistics infrastructure is a key factor in creating smooth flow of goods. Thus, the central government has built various logistic supporting facilities, such as Regional Distribution Center (RDC). However, this RDC has not optimaly functioned since the management of the RDC is not effective and efficient. The alternative solution to this issue may be the Public- Private Partnership (PPP) management. There are some types of PPP to choose in order to run the RDC management. Yet, the process of selection may be a little complex because it involves several stakeholders. Each type has its own characteristics. The selection must take into consideration the many affecting or affected criteria. This research aims to create a selection method base on Multi Criteria Decision Making (MCDM). Analytic Network Process (ANP) technique is used to solve the complexity of inter- affecting criteria. The preceding research has designed a MCDM-based selection method but the method mostly considered the decision-maker interest. There is also a research which designed the partnership scheme involving external parties interests but it did not develop the selection method. This research did both i.e. developing method of partnership selection while considering both external and internal parties. The ANP technique is applied as described in the procedure designed by Thomas L. Saaty. Relevant criteria are generated from references study then validated by expert (expert judgement). The chosen criteria are: expected performance, fulfilling the needs of all parties, impact to environment/state condition, recent RDC management, institutional capability, and available PPP types. A network representing all connections emerging between and inside the criteria is made to create a model of ANP network to select PPP type. A case study was done in South Sulawesi RDC. The basic types made by Asian Development Bank is clarified using business process so the respondents are able to compare one type to the others and make the best option. Benchmarking was done to management of public goods distribution and the practice of PPP which has been sucessfully applied in the country and abroad. It resulted in the six business process alternative charts of PPP i.e. service contract, management contract, lease contract, concession contract, BOT contract, and joint venture. Pairwise comparison questionnaire was arranged based on the settled network. A survey was then done to selected respondents representing central government, local government, and private sector. The data were then processed using Super Decision for ANP Version 2.2. software. The result showed that the priority of PPP type in operation of South Sulawesi RDC was as follows: concession contract (0,19066); joint venture (0,18619); service contract (0,18313); management contract (0,18186); BOT contract (0, 14895); and lease contract (0,10922). This method of selection can be applied and/or developed for any RDC in other locations.